Comparative analysis of short-term efficacy between robot-assisted retrograde drilling and arthroscopic microfracture for osteochondral lesions of the talus - Chen, Xiao Qiang; Liu, Jianquan; Wang, Tianyu; Zhao, Zhe; Li, Yongsheng; Cheng, Xiang Yu; Li, Wencui (Frontiers in Surgery, 2024)
1. Background and Significance:Osteochondral lesions of the talus (OCLT) are lesions involving the articular cartilage and subchondral bone of the talus, most of which are associated with chronic micro-injuries following ankle trauma and are prevalent in the athletic population. As previously reported, approximately 50% to 73% of patients already have OCLT at initial diagnosis of acute ankle sprain and then develop typical clinical and imaging manifestations over time. In this paper, a novel surgical procedure is introduced from the perspective of surgical robots involved in the minimally-invasive treatment of early OCLT and the experience and gains of our team are reported. 2.Novelties:The application of surgical robots in the field of ankle surgery has rarely been reported. It is believed that surgical robots will be more and more involved in foot and ankle surgery and even orthopedic surgery with further development of the technology and concept. Thus, the application of robot-assisted surgical treatment for early OCLT was expounded in this paper.